PENGECATAN WATER TRANSFER PRINTING FILM MENGGUNAKAN TEKNOLOGI SEMI OTOMATISARDUINO UNO R3: PENGECATAN WATER TRANSFER PRINTING FILM MENGGUNAKAN TEKNOLOGI SEMI OTOMATISARDUINO UNO R3 - Rifai, Muhammad (Jurnal Rekayasa Mesin, 2020)
There have been many painting media on the market, but there are still many who use manual painting systems. For that, a tool system for painting water transfer printing film using semi-automatic technology Arduino Uno R3. This tool can provide ease in painting techniques, which was previously done manually. In this design, use a servo motor to read the program inserted into the Arduino Uno R3, equipped with LCD as a screen display and to enter the program code used KEYPAD 4x4. This research is the development research aimed at the best results on the film and Activator pattern in order to obtain an effective comparison when painting. After the process is done development and testing known tools work well. As for the best results visually, namely, the pattern film size is 15.5 cm2, for Activator as much as 4 ml and one time the painting process takes 1 minute 14 seconds. Keywords: Microcontroller arduino, Arduino uno R3, water transfer printing technique of film.